The Influence of Temperature on the Microstructure, Atterberg Limits, and Swelling Pressure of Bentonite Clay: A Review - Lingling Li; Haiquan Sun; Xiaoyu Fang; Liangliang Lu (Geosciences, 2025)
The geological containment of high-level radioactive waste has become widely accepted among international organizations, and it has been adopted by many countries as part of their national nuclear waste disposal plan. The multi-barrier system, including the compacted bentonite blocks or pellets serving as human-made containment or buffer media, is the key component of high-level radioactive waste disposal, which contains a waste canister that isolates the nuclear waste from a human being geosphere for one million years. The bentonite clay surrounding the nuclear waste capsule is subjected to prolonged exposure to elevated temperatures because of the continuous decay of radioactivity. Long-term heating at high temperatures could change the buffers’ microstructural characteristics and physicochemical and hydromechanical properties, which can influence their self-sealing ability. This paper offers a comprehensive overview of the current understanding of thermal effects on bentonite-based buffer systems. The thermal impact on the microstructure, Atterberg limits, and swelling pressure of bentonite clay are intensely reviewed, and the findings are summarized. This review paper highlights new insights into the design of multi-layered containment approaches for high-level radioactive waste isolation.